Muscle Quality, Measured by Ultrasound-Derived Corrected Echo Intensity, Does not Affect Changes in Cross-sectional Area of the Vastus Lateralis Following Recumbent Rest. (March 2021) - Varanoske, Alyssa N.; Coker, Nicholas A.; Johnson, Bri-Ana D. I.; Belity, Tal; Wells, Adam J.
Objective: Recumbent rest elicits a decrease in muscle size of the lower extremity, but the extent of decrease may be related to differences in muscle quality. This could have implications for ultrasound-derived measures of muscle size, particularly in individuals with a large proportion of intramuscular contractile elements. The research objective was to determine whether decreases in muscle size following recumbent rest are related to ultrasound-derived corrected echo intensity in resistance-trained males. Methods: Cross-sectional area (CSA), echo intensity (EI), subcutaneous fat thickness (SFT), and EI corrected for SFT (EICor ) of the vastus lateralis (VL) were measured via ultrasonography in 30 resistance-trained males. Measures were obtained immediately following recumbency (T0) and 15 minutes after recumbency (T15). The association between EICor and percentage change in CSA (%ΔCSA) from T0 to T15 was examined. Comparisons of morphological characteristics were examined between a subset of participants with the lowest (LO; n = 10; <33rd percentile) and highest (HI; n = 10; >66th percentile) EICor . Results: EICor was not correlated with %ΔCSA ( P = .151), and the decrease in CSA from T0 to T15 did not differ between the LO and HI groups. Conclusions: Muscle quality (EICor ) is not related to the decrease in CSA of the VL following recumbent rest among resistance-trained, young males. The time frame of muscle CSA acquisition should not differ based solely on differences in muscle quality.